Pamali: Intervensi dan Pengaruhnya terhadap Pembentukan Pola Pikir Logis Remaja dalam Masyarakat Banjar - Sriwati, Sriwati; Prasetyo, Wawan; Iqbal, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Pamali is one of the rules in society that is socialized and taught by parents to children in the form of prohibitions accompanied by threats with the intention of making it a control over children's behavior. Every parent's advice certainly has a good intention, but often the prohibitions that are collected in the pamali category are difficult to understand and even there is no relevance between cause and effect if violated. However, this tradition is able to intervene and influence the logical thinking ability of adolescents in Banjar society. The type of research used is descriptive qualitative. The research subjects included some students of SMA Global Islamic Boarding School. The technique used in retrieval of information is purposive sampling, namely by taking research subjects who meet the following criteria: 1) students who are familiar with the term pamali, 2) students born in the Banjar community, 3) students who are included in the category of having a high and low logical mindset. The results showed that the pamali tradition as folklore has a vital role in influencing the logical thinking patterns of adolescents. This is shown by their fear which is more dominant than their belief in the pamali tradition. Teenagers who believe in the pamali tradition tend to have an excessive fear of the consequences that do contain a lot of bad luck in it. Adolescents who have low logical thinking skills tend to believe in the pamali tradition. Then when compared to teenagers who have good logical thinking skills, they tend to be better able to filter the impact of the pamali tradition.